305 The INVEST Trial: A Randomized, Controlled Trial to Investigate the Safety and Efficacy of Image-Guided Minimally Invasive Endoscopic Surgery With Apollo vs Best Medical Management for Supratentorial Intracerebral Hemorrhage. (August 2016) - Fiorella, David; Arthur, Adam S.; Mocco, J.D.
Abstract : INTRODUCTION: Spontaneous intracerebral hemorrhage (ICH) is a common subtype of hemorrhagic stroke, with the poorest prognosis of all stroke subtypes. Today's standard of care for these patients result in high mortality, lengthy recovery times, and low functional improvements. The goal of the INVEST trial is to evaluate the safety and efficacy of minimally invasive hemorrhage evacuation with the Apollo device (Penumbra Inc, Alameda, California) compared with medical management. METHODS: The INVEST study is a prospective multicenter US trial designed to enroll 222 patients at up to 30 centers. Patients between the ages of 22 and 80 or <85 with baseline modified Rankin Scale (mRS) = 0 or 1, National Institutes of Health Stroke Scale of at least 6, Glasgow Coma Scale of 5 to 15, and presenting with a moderate to large-volume supratentorial ICH (30-80 cm 3 ) within 24 hours of onset are eligible for enrollment. Qualifying patients will be randomly assigned (1:1) to either minimally invasive surgery (MIS) with Apollo or to best medical management (MM) following a stability scan. Follow-up for each patient will be conducted at days 3, 7, discharge, 30, 90, 180, and 360 from enrollment. The primary end points are mRS 0 to 3 at 180 days and mortality at 30 days. Secondary end points include stroke impact scale (SIS) mobility, SIS-activities of daily living, and EQ-5D-5L at 180 days, and length of hospitalization. All imaging will be assessed by an independent core laboratory. RESULTS: Centers are currently in the process of initiation with a potential start date forthcoming. Updated information regarding trial progress will be discussed at the time of presentation. CONCLUSION: The INVEST is designed to provide an assessment of the safety and efficacy of Apollo MIS for the treatment of spontaneous supratentorial ICH.